2012
DOI: 10.1007/s00384-011-1403-5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical versus nonanatomical resection of colorectal liver metastases: a meta-analysis

Abstract: NAR is a safe procedure for CLM and does not compromise oncological outcomes. However, the findings have to be carefully interpreted due to the lower level of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Non‐anatomical hepatectomies should therefore be preferred, saving the maximum amount of non‐tumoral liver parenchyma, provided that safe tumour margins can be achieved. This practice is supported by the fact that wedge resections provide the same oncological benefit as anatomical resections.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐anatomical hepatectomies should therefore be preferred, saving the maximum amount of non‐tumoral liver parenchyma, provided that safe tumour margins can be achieved. This practice is supported by the fact that wedge resections provide the same oncological benefit as anatomical resections.…”
Section: Discussionmentioning
confidence: 99%
“…This paradigm shift in management of CRLM from ‘what comes out’ to ‘what stays in’ has led to non‐anatomical resections (NARs) being increasingly utilized. Several studies, comparing anatomical and non‐anatomical liver sparing surgery have published conflicting results with some showing better survival with AR, whilst others showed no difference although, a recent meta‐analysis comparing the two techniques has shown that margins and oncologic outcomes were comparable . Nevertheless, the majority of studies in the meta‐analysis were non‐randomized and included small numbers of participants.…”
Section: Introductionmentioning
confidence: 99%
“…9 At the same time, it had been demonstrated that anatomic resection had no benefit over smaller, nonanatomic resection in CRLM, and that parenchymal sparing had paramount importance, both to increase safety, and "keep the door open" for future resections. 22 Although these trends-small margins, nonanatomic resections and parenchymal sparing-did not result in compromised oncological outcomes, [22][23][24] the benefit as well as impact of R1 resection on disease progression, control of liver disease and OS is less clear, and is difficult to assess, given the paucity of prospective data on the matter. resections, indicates that R1 resection may be worth pursuing, whenever an R0 is not feasible, and the surgical risk is acceptable.…”
Section: Discussionmentioning
confidence: 99%